Analysis and prediction of student placement for improving the education standards - Anjali Devi, S; Vishnu Priya, M; Akhila, P; Vasundhara, N (International Journal of Engineering and Technology, 2018)
Studentsâ€™ academic success can be evaluated based on their performance in the exams conducted by the institutions. In this paper, we propose a scheme where prediction of student final placement can be done based on the marks scored by them in the previous semesters. In order to predict the placement of the student we need some data to analyze. For this purpose we will supply students basic details and their previous academic information into the system which will be used to predict the placement of the student. This is done by generating association rules using apriori algorithm. Admin and user will use this system. Here user will be the student. Admin and user will use their login to access the system. Admin will add academic details of the students, like their SSC, HSC, Graduation marks (up to current semester, Back logs etc.,). User will be the student. Admin and user will use their login to access the system. Admin will add academic details of the students, like their SSC, HSC, Graduation marks (up to current semester, Back logs etc.,).Â  This system can be used in schools, colleges and other educational institutions. This evaluation system is more accurate than other conventional methods. We are using a university data set to predict the placement of the student.